Distribution. From N in Cricetidae ... - Wilson, Don E.; Mittermeier, Russell A.; Thomas E. Lacher, Jr (Zenodo, 2017)
Distribution. From N Iberian Peninsula throughout most of Europe N & W to Denmark, SE Finland, and W European Russia, and SE to Macedonia and Bulgaria; also isolated populations on Is off the Atlantic coast of France (Noirmoutier, Yeu, and Oléron), Orkney Is in the N coast of Great Britain, Guernsey in the ChannelIs, several Is in the Wadden Sea off the NW coast of Germany, and Is off the W coast of Estonia. ... : Published as part of Don E. Wilson, Russell A. Mittermeier & Thomas E. Lacher, Jr, 2017, Cricetidae, pp. 204-535 in Handbook of the Mammals of the World – Volume 7 Rodents II, Barcelona :Lynx Edicions on page 351, DOI: 10.5281/zenodo.6707142 ...